Endothelial Activation and Microcirculatory Disorders in Sepsis - Raia, Lisa; Zafrani, Lara (Frontiers in Medicine, 2022)
The vascular endothelium is crucial for the maintenance of vascular homeostasis. Moreover, in sepsis, endothelial cells can acquire new properties and actively participate in the host’s response. If endothelial activation is mostly necessary and efficient in eliminating a pathogen, an exaggerated and maladaptive reaction leads to severe microcirculatory damage. The microcirculatory disorders in sepsis are well known to be associated with poor outcome. Better recognition of microcirculatory alteration is therefore essential to identify patients with the worse outcomes and to guide therapeutic interventions. In this review, we will discuss the main features of endothelial activation and dysfunction in sepsis, its assessment at the bedside, and the main advances in microcirculatory resuscitation